The Analysis of Land Use Change of Mangrove Ecosystem in Langkat, North Sumatera, Indonesia - Ginting, Surya Dharma; Rauf, Abdul; Rahmawaty (Journal of Environmental and Development Studies, 2023)
Mangroves are subtropical and warm temperate intertidal ecosystems that sustain the well-being of humans and wildlife through a variety of services. However, the existence of mangroves is presently threatened by alterations in land use. From 2010 to 2022, mangrove areas in Pasar Rawa Village, Gebang District, Langkat Regency, North Sumatra province have decreased significantly. The destruction of mangrove forests is primarily caused by the neighboring community's activities. The purpose of this study was to assess the level of damage and density of mangroves in Pasar Rawa Village, as well as to examine the perceptions of locals regarding the management of mangrove ecosystems. The investigation was carried out from January to March 2023 by distributing the questionnaires to the 286 respondents. Based on the vegetation analysis and indexing vegetation analysis through Landsat 7 and Landsat 8 image processing, the amount of mangrove areas in Pasar Rawa Village decreased by 52.97 ha between 2010 and 2022, with the majority of mangrove areas being converted into oil palm plantations and fish farming ponds. It is dominated by the dense class of the Normalized Difference Vegetation Index (NDVI) in 2022, despite the condition of the mangroves in Pasar Rawa Village still being classified as damaged during this recovery process. In addition, the outcome of public perception demonstrates that the management of the mangrove ecosystem is suitable and supports the capacity to create a sustainable mangrove ecosystem.